Borden's American Dairy Company - Gordon, John C. (photographer):::Creator::::::::::::
Storefront with neon sign that reads, "Borden's American Dairy Company, milk - ice cream". Under the sign is a man on a horse, a man standing and four women in cowboy costumes.